Association between salivary /microbiological parameters, oral health and eating habits in young athletes - Domenico Tripodi; Alessia Cosi; Rosita Valloreo; Domenico Fulco; Marco Tieri; Lavinia Alberi Auber; Simonetta D’Ercole (Journal of the International Society of Sports Nutrition)
Background Athletes’ oral health can impact overall well-being and sports performance. This study aimed to evaluate the interactions between eating habits and oral health of 120 young athletes as compared to 30 age-matched individuals not practicing sports based on a questionnaire and the analysis of saliva.Methods One hundred twenty subjects practicing various sports activities (test group) and 30 subjects not practicing sports (control group) were selected. A self-administered questionnaire was used to obtain personal data, hours and frequency of weekly training, complete pathological history, history of hard and soft tissues of the oral cavity, family history, and oral hygiene practices. The eating habits of the young participants were analyzed by investigating the number of daily meals; use and frequency in sports practice of supplements/energy drinks, fruit/juices, snacks, chocolate; daily diet; and differences between usual diet and pre-competition diet. At baseline (T0), each participant was clinically assessed for the determination of the number of decayed, missing, and filled teeth (DMFT), Silness & Löe Plaque Index (PI), and the Löe & Silness Gingival Index (GI) and qualitative analysis for the presence/absence of stains and dental erosions. At T0, before (T1) and after training sessions (T2), saliva was collected to determine resting pH, Streptococcus mutans, and Lactobacillus spp counts.Results Test groups were trained more than 2 h, 5 times a week. Soccer players and skiers had a high percentage of caries; water polo players demonstrated the highest percentage of erosions and dental stains. Salivary resting pH showed statistically different values in three different observations between the groups. S. mutans was harbored by 60% of soccer and 70% of water polo players, while Lactobacillus spp in 43.33% of the swimmers and soccer players. Combining all the 56 variables including the clinical examination, self-reported parameters, and salivary analysis, we have identified water polo players as a distinct at-risk group for developing dental defects, expressed as an aggregate disease score. In particular, we have found that energy snacks/chocolate intake is strongly associated with ratio of S. mutans/Lactobacillus spp and that S. mutans is linked to dental defects (R = 0.88). Linear regression analysis indicates that energy snacks/chocolate intake in the study population represents a strong driver for oral dysbiosis and dental disease.Conclusions Our study clearly shows that athletes should follow a balanced diet that not only satisfies their nutritional needs but also avoids oral dysbiosis and subsequent dental damage.